The Influence of E1A C-Terminus on Adenovirus Replicative Cycle - Leandro Crisostomo; Andrea Michelle Soriano; Jasmine Rae Frost; Oladunni Olanubi; Megan Mendez; Peter Pelka (Viruses, 2017)
Adenovirus Early 1A proteins (E1A) are crucial for initiation of the viral life cycle after infection. The E1A gene is encoded at the left end of the viral genome and consists of two exons, the first encoding 185 amino acids in the 289 residues adenovirus 5 E1A, while the second exon encodes 104 residues. The second exon-encoded region of E1A is conserved across all E1A isoforms except for the 55 residues protein, which has a unique C-terminus due to a frame shift following splicing into the second exon. This region of E1A contributes to a variety of processes including the regulation of viral and cellular gene expression, immortalization and transformation. Here we evaluated the contributions that different regions of the second exon of E1A make to the viral life cycle using deletion mutants. The region of E1A encoded by the second exon was found to be important for overall virus growth, induction of viral and cellular gene expression, viral genome replication and deregulation of the cell cycle. Efficient viral replication was found to require exon 2 and the nuclear localization signal, as loss of either resulted in severe growth deficiency. Induction of cellular DNA synthesis was also deficient with any deletion of E1A within the C-terminus even if these deletions were outside of conserved region 4. Overall, our study provides the first comprehensive insight into the contributions of the C-terminus of E1A to the replicative fitness of human adenovirus 5 in arrested lung fibroblasts.